Sky the unwanted kitten - Webb, Holly; Williams, Sophy (New York : Scholastic, 2010)
Lucy is unhappy about having to move and leave all her friends behind. Her parents hope that a cat will help her to settle in, so they surprise her with Sky--a gorgeous Siamese kitten. --Cover.
Keywords: Kittens -- Juvenile fiction